Analysis of the Effect of Compensation and Motivation on Organizational Performance through Employee Performance - Siti Lomyati; Hermien Tridayanti (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The purpose of this research is to know and analyze the effect Compensation and Motivation on Organizational Performance through Employee Performance, Compensation for employee performance, Motivation for employee performance, Compensation for Organizational Performance and Motivation for Organizational Performance. Design/methodology/approach: Data collection techniques using filling out questionnaires with a quantitative methodology which is distributed to the sample population of 160 employees and processed using the Amos ver 26 application. Findings: The research results show that there is a significant effect of compensation on employee performance, as well as motivation has a significant effect on employee performance, and there is also a significant effect of compensation on organizational performance, as well as motivation has a significant effect on organizational performance. Paper type: Research paper